GMT-based geological mapping and assessment of the bathymetric variations of the Kuril-Kamchatka Trench, Pacific Ocean - Lemenkova, Polina (2020)
This manuscript summarizes the results of the geospatial analysis undertaken by means of Generic Mapping Tools (GMT). The comparative assessment of the bathymetry of the Kuril-Kamchatka hadal trench was performed for southern and northern segments separated by the Bussol Strait. The formation of the hadal trench is affected by the impacts of local geological and geophysical settings varying along the trench. The methodological approach is as follows. The profiling was undertaken using GMT modules ‘grdimage’, ‘grdtrack’ and ‘psxy’. The modelling consists of the collected data of 10706 observation samples from 52 profiles in southern part and 12726 from 62 profiles in the northern segment. The GMT modules ‘psrose’ and ‘pshistograms’ were used to plot histograms and rose diagrams visualizing bathymetric variables of depths. The geology was mapped using GMT modules ‘pscoast’, ‘grdcut’, ‘grdcontour’ and ‘psxy’ to plot lineaments and geological objects (ophiolites, faults, earthquakes, trench, magnetic anomalies, tectonic slabs, fracture zones and volcanoes). The base map is based on the ETOPO Global Relief Model. The comparison of the bathymetry shown variations in the northern and southern segments: southern part reaches -8,200 m maximal depths while northern has -7,800 m. This is influenced by the geological settings: earthquakes magnitude and seismisity are higher in the south-west. The submarine terraces and floodplains were observed at -4000 m depth forming landforms located southwards off the Bussol Strait. This geospatial analysis contributes to the development of the geological mapping with an example of the Kamchatka area, a region with high seismisity and repeated earthquakes. info:eu-repo/semantics/published